Beyond Smoke and Mirrors : climate change and energy in the 21st century - Richter, Burton. 1931- (Cambridge, UK ; New York : Cambridge University Press, 2010)
"Global climate change is one of the most important issues humanity faces today. This book assesses the sensible, senseless and biased proposals for averting the potentially disastrous consequences of global warming, allowing the reader to draw their own conclusions on switching to more sustainable energy provision. Burton Richter is a Nobel Prize-winning scientist who has served on many US and international review committees on climate change and energy issues. He provides a concise overview of our knowledge and uncertainties within climate change science, discusses current energy demand and supply patterns, and the energy options available to cut emissions of greenhouse gases. Written in non-technical language, this book presents a balanced view of options for moving from our heavy reliance on fossil fuels into a much more sustainable energy system, and is accessible to a wide range of readers without scientific backgrounds - students, policymakers, and the concerned citizen"--Provided by publisher.
Preface; List of units; List of conversion factors; List of abbreviations; 1. Introduction; Part I. Climate: 2. Greenhouse Earth; 3. Climate modelling; 4. The past as proxy for the future; 5. Predicting the future; Part II. Energy: 6. Taking up arms against this sea of troubles; 7. How fast to move: a physicist's look at the economists; 8. Energy, emissions and action; 9. Fossil fuels: how much is there?; 10. Electricity, emission and pricing carbon; 11. Efficiency: the first priority; 12. Nuclear energy; 13. Renewables; 14. Biofuels: is there anything there?; 15. An energy summary; Part III. Policy: 16. US policy: new things, bad things, good things; 17. World policy action; 18. Coda; References; Index.
Includes bibliographical references (p. 219-221) and index.
Keywords: Climatic changes -- Forecasting; Renewable energy sources -- Forecasting; Twenty-first century -- Forecasts